2021
DOI: 10.3991/ijim.v15i04.20291
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies in Education 4.0. Does it Enhance the Effectiveness of Learning? A Systematic Literature Review

Abstract: <p class="0abstract"><strong>Abstract—</strong> Over the past decade, digitalization shapes the overall educational structure worldwide, with the attention received from practitioners, researchers, and policymakers for educational development.   Digital technologies are bringing massive changes across education, skills, and employment. These changes mirror how technology is increasingly central to education 4.0. Digital technologies are expanding beyond innovative and less traditional techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 31 publications
(31 reference statements)
1
67
0
4
Order By: Relevance
“…The main agenda is to find the direction and improvement of research related to the educational structure and change in the learning process of digital technologies. The recent development of digital technologies in many fields is prompting researchers to improve the quality of instruction by using these resources [1]. The Office of the Higher Education Commission (OHEC), Ministry of Education, in collaboration with the Office of the Permanent Secretary of the Ministry of Information and Communication Technology, has set up a project to develop Thai e-universities and is pioneering the development of a central system for Thailand's massive open online courses (MOOCs).…”
Section: Introductionmentioning
confidence: 99%
“…The main agenda is to find the direction and improvement of research related to the educational structure and change in the learning process of digital technologies. The recent development of digital technologies in many fields is prompting researchers to improve the quality of instruction by using these resources [1]. The Office of the Higher Education Commission (OHEC), Ministry of Education, in collaboration with the Office of the Permanent Secretary of the Ministry of Information and Communication Technology, has set up a project to develop Thai e-universities and is pioneering the development of a central system for Thailand's massive open online courses (MOOCs).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a common recommendation in many studies was to provide psychological support and training in coping strategies [8], [26], [27], [43], [47]. Other recommendations included: screening medical staff at high risk of stress to offer them psychological support, daily monitoring of HCWs emotional status, reducing the intensity of work and engaging HCWs in strengthening exercise program [25], [34], [43], [48], [49], [50].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, these services could be improved by using both direct clinical experience and formal hands on training [8]. Thirdly, it is recommended to follow the published and proven protocols and guidelines in assessing and treating patients [40], [38,39]. Lastly, it is found that the relations between the clients and clinic operators in addition to the inter-professional teamwork are key contributors of operationalizing the Tele-Health services [41].…”
Section: Discussionmentioning
confidence: 99%